2022
DOI: 10.1002/pssr.202200365
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Carrier Mobility in Cd3As2 Nanowires

Abstract: Magnetotransport measurements are carried out on nanowires of the Dirac semimetal . Weak antilocalization is observed at 1.9 K, consistent with the presence of strong spin–orbit interaction. With decreasing temperature, Shubnikov–de Haas oscillations are seen, revealing an ultrahigh mobility of 57 000 cm2 Vs at 1.9 K. The strong oscillations display a linear dependence of the Landau‐level index on the inverse of the magnetic field, yielding an intercept that is consistent with a π Berry phase—the signature fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…However, the non-centrosymmetric nanowire ensemble displays a higher peak emission frequency (~1.5 THz) compared to the centrosymmetric single crystal (~0.8 THz), indicating a shorter relaxation time. Previous magneto-transport and terahertz spectroscopic studies on Cd3As2 nanowire ensembles have also demonstrated a transition from the metallic behavior observed in bulk crystals and thin films to semiconducting behavior [5,6]. This semiconducting behavior could also account for the higher peak emission frequency.…”
Section: Resultsmentioning
confidence: 83%
“…However, the non-centrosymmetric nanowire ensemble displays a higher peak emission frequency (~1.5 THz) compared to the centrosymmetric single crystal (~0.8 THz), indicating a shorter relaxation time. Previous magneto-transport and terahertz spectroscopic studies on Cd3As2 nanowire ensembles have also demonstrated a transition from the metallic behavior observed in bulk crystals and thin films to semiconducting behavior [5,6]. This semiconducting behavior could also account for the higher peak emission frequency.…”
Section: Resultsmentioning
confidence: 83%